2021
DOI: 10.1108/jpbm-08-2020-3047
|View full text |Cite
|
Sign up to set email alerts
|

Conspicuous consumption of luxury experiences: an experimental investigation of status perceptions on social media

Abstract: Purpose As luxury goods are losing their importance for demonstrating status, wealth or power to others, individuals are searching for alternative status symbols. Recently, individuals have increasingly used conspicuous consumption and displays of experiences on social media to obtain affirmation. This study aims to analyze the effects of luxury and nonluxury experiences, as well as traditional luxury goods on status- and nonstatus-related dimensions. Design/methodology/approach After presenting the theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 119 publications
0
26
0
Order By: Relevance
“…This is illustrated by one of the cluster’s most-cited articles, “Consumer engagement in online brand communities: A social media perspective” (TC = 488), published by a research group comprising Dessart et al (2015). Most articles in this cluster have gone into great depth on how corporate brands have (or may) simplify their interactions and activities to provide the best customer experience possible both before and after the purchase (Siepmann et al , 2021; Yang and Mundel, 2021). Furthermore, other articles have highlighted how brand owners have (or may) use a range of various communication methods to nurture client connections, enhance customer happiness and actively retain a customer base (Areni, 2021; Jacobson, 2020; Villegas and Marin, 2021).…”
Section: Science Mapping Of Journal Of Product and Brand Managementmentioning
confidence: 99%
“…This is illustrated by one of the cluster’s most-cited articles, “Consumer engagement in online brand communities: A social media perspective” (TC = 488), published by a research group comprising Dessart et al (2015). Most articles in this cluster have gone into great depth on how corporate brands have (or may) simplify their interactions and activities to provide the best customer experience possible both before and after the purchase (Siepmann et al , 2021; Yang and Mundel, 2021). Furthermore, other articles have highlighted how brand owners have (or may) use a range of various communication methods to nurture client connections, enhance customer happiness and actively retain a customer base (Areni, 2021; Jacobson, 2020; Villegas and Marin, 2021).…”
Section: Science Mapping Of Journal Of Product and Brand Managementmentioning
confidence: 99%
“…Further, materialistic individuals display their status, wealth and uniqueness in order to impress others [ 26 ] by using products to disclose information about themselves [ 27 ]. Thus, materialism had an impact on the status perception of individuals on SNS [ 28 ]. Besides, recent research on trait materialism has also shown the influence on posting behaviour [ 29 ], e-WOM diffusion [ 30 ], and SNS intensity among users [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…While social media consumption lacks the actual good to consume, Siepmann et. al (2021) found, that seeing an experience on Instagram was perceived as a means of status building and selfactualization comparable to the actual use of a good.…”
Section: Introductionmentioning
confidence: 99%
“…So, a large part of the research on the connection between conspicuous consumption and social media has focused on fitness. But many studies focus on differences between genders (e.g., Mujcic & Frijters, 2015;Siepmann, et al, 2021) or the progress of tribalization (Lamb & Hillman, 2015;Stollfuß, 2020). However, during the recent Covid-19pandemic, another important factor emerged: the location.…”
Section: Introductionmentioning
confidence: 99%